An Examination of Mobile Spinal Cord Stimulators on Treating Parkinson Disease - Wang, Zhen-Jie (Brain Circ, 2021)
In animal models of Parkinson disease (PD), spinal cord stimulation (SCS) exhibits neuroprotective effects. Recent advancements in SCS technology, most importantly mobile stimulators, allow for the conventional limitations of SCS such as limited stimulation time and restricted animal movements to be bypassed, offering potential avenues for improved clinical translation to PD patients. Small devices that could deliver continuous SCS to freely moving parkinsonian rats were shown to significantly improve behavior, preserve neurons and fibers in the substantia Nigra/striatum, reduce microglia infiltration, and increase laminin-positive area of the cerebral cortex. Through possible anti-inflammatory and angiogenic mechanisms, it has been demonstrated that there are behavioral and histological benefits to continuous SCS in a time-dependent manner. This review will discuss the benefits of this technology as well as focus on the limitations of current animal models.